2018
DOI: 10.1002/jsfa.9102
|View full text |Cite
|
Sign up to set email alerts
|

Dark chocolate with a high oleic peanut oil microcapsule content

Abstract: The products obtained have a desirable quality and physical properties, being suitable for industrial production. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…Considering its high consumption, it seemed as a reasonable option to fortify chocolate with different bioactive compounds as a delivering agent. Previous studies showed that fortifying chocolate with high oleic peanut oil, phytosterols, cinnamon bark oleoresin, chia seed oil microcapsules can provide a stable and acceptable final product ( Agibert and Lannes, 2018 , Tolve et al, 2018 , Praseptiangga et al, 2019 , Razavizadeh and Tabrizi, 2021 ). Moreover, the knowledge gained from the study of Toker et al (2018) showed that incorporation of encapsulated forms of EPA/DHA (commercial microencapsulated powder based on fish gelatin) in dark chocolate represents the best option in terms of product quality compared to other forms (free-flowing powder, nutritional oil derived from algae, triglycerides).…”
Section: Introductionmentioning
confidence: 99%
“…Considering its high consumption, it seemed as a reasonable option to fortify chocolate with different bioactive compounds as a delivering agent. Previous studies showed that fortifying chocolate with high oleic peanut oil, phytosterols, cinnamon bark oleoresin, chia seed oil microcapsules can provide a stable and acceptable final product ( Agibert and Lannes, 2018 , Tolve et al, 2018 , Praseptiangga et al, 2019 , Razavizadeh and Tabrizi, 2021 ). Moreover, the knowledge gained from the study of Toker et al (2018) showed that incorporation of encapsulated forms of EPA/DHA (commercial microencapsulated powder based on fish gelatin) in dark chocolate represents the best option in terms of product quality compared to other forms (free-flowing powder, nutritional oil derived from algae, triglycerides).…”
Section: Introductionmentioning
confidence: 99%
“…Many researches are being developed using the microencapsulation method. Thus, to protect oils from lipid oxidation [34][35][36], incorporating functional ingredients such as vitamins [37,38], additives and their storage protection [38], antioxidant protection [39].…”
Section: Instantizationmentioning
confidence: 99%
“…Carvalho et al (2018) added grape and kale to improve the milk chocolate nutritional role. Agibert & Lannes (2018) improved the nutritional value of chocolate adding high oleic peanut oil microcapsule.…”
Section: Introductionmentioning
confidence: 99%